High‐performance counter electrode based on nitrogen‐doped porous carbon nanoribbons for quantum dot‐sensitized solar cells. (14th April 2020) - Dong, Weinan; Liu, Jieqiong; Wang, Guiqiang
Summary: Nitrogen‐doped porous carbon nanoribbons (NPCNs) are facilely prepared by carbonization of polypyrrole (PPy) nanotubes followed by a chemical activation process. NPCN counter electrodes are subsequently fabricated by depositing NPCNs onto Ti mesh for quantum dot‐sensitized solar cells (QDSCs). Electrochemical tests are carried out to evaluate the electrocatalytic performance of obtained NPCN electrode. The data of electrochemical tests suggest that the NPCN electrode has a superior electrocatalytic ability towards polysulfide ( S 2 2− / S 2− ) electrolyte regeneration reaction and displays a high stability in polysulfide electrolyte. The excellent electrocatalytic performance of NPCN electrode can be ascribed to their large surface area, 2D porous nanoribbon morphology, and nitrogen atom doping, which provides abundant electrocatalytic active sites and facilitates the electrolyte diffusion. Consequently, a power conversion efficiency of 3.27% is obtained by using NPCN electrode as the counter electrode for QDSC. This efficiency is close to the QDSC assembled with commonly used PbS electrode (4.0%). Abstract : Nitrogen‐doped porous carbon nanoribbons (NPCNs) with high surface area are facilely prepared and explored as the counter electrode of quantum dot‐sensitized solar cells. The combined effect of nitrogen doping, high surface area, and 2D porous nanoribbon morphology endow NPCN counter electrode with superior electrocatalytic activity for the reduction of polysulfide electrolyte.